WIDENING ECONOMIC DISPARITIES IN INDIA: CHALLENGE FOR INCLUSIVE DEVELOPMENT - Yadav, Dr. Anil Kumar (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
The Indian growth story has been far from perfect. That is not an understatement by any stretch of imagination. A growing challenge for the economy is the fast-evolving problem of inequality. Most recently, James Crabtree in his latest book, "The Billionaire Raj", claims that "India is one of the world's most unequal countries." His claim is based on the fact that the billionaire wealth as a proportion of the entire country's output is the highest for India, except for Russia. The latest human development rankings released last week also corroborate his findings. India already ranks a lowly 130 on the index out of 189 countries but when adjusted for inequality, the scores experience a drastic fall of almost 27 percent against a world average of 20 percent. What explains India's dismal performance on the inequality front? Why don't other developing countries face a similar problem? To put it simply, economic growth in India has not been inclusive enough. All the hype about the country's fast-paced economic growth has not percolated down through the economy.